Comparative study of commercial bank's credit risk in Malaysia - Ho, Tai Yu; Lau, Ching Keat; Seet, Xian Zhe; Wee, Zhen Vern; Wong, Zhi Qing (2020)
This research paper focuses on examining the independent variables affecting Non- Performing Loan (NPL) banks in Malaysia. Bank size, bank profitability, cost efficiency interest rate and unemployment rate are the variables that will be used to conduct the research. Data of variables was collected on quarterly basis from year 2010 to 2018, consisting sample size of 36 observations for each variable. Data was obtained from Bank Negara Malaysia (BNM) statistics database and The World Bank statistics database. Impulse response function will be used for this research and Econometrics View (EViews) program will be used to test the presence of econometrics problem. The results of the research revealed that all independent variable are significant towards the NPLs.